2015
DOI: 10.1044/2015_jslhr-h-15-0043
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hearing Aid Use on Outcomes of Children With Mild Hearing Loss

Abstract: Purpose: This study examined the effects of consistent hearing aid (HA) use on outcomes in children with mild hearing loss (HL). Method: Five-or 7-year-old children with mild HL were separated into 3 groups on the basis of patterns of daily HA use. Using analyses of variance, we compared outcomes between groups on speech and language tests and a speech perception in noise task. Regression models were used to investigate the influence of cumulative auditory experience (audibility, early intervention, HA use) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
3
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 55 publications
7
113
3
6
Order By: Relevance
“…Recent evidence from the Outcomes of Children with Hearing Loss (OCHL) study suggest that consistent HA use may reduce the risk of negative outcomes in children with mild HL (Walker, Holte, et al, 2015). Walker, Holte, et al found a positive association between amount of daily HA use and language outcomes.…”
Section: Developmental Outcomes and Service Provision In Children Witmentioning
confidence: 94%
See 2 more Smart Citations
“…Recent evidence from the Outcomes of Children with Hearing Loss (OCHL) study suggest that consistent HA use may reduce the risk of negative outcomes in children with mild HL (Walker, Holte, et al, 2015). Walker, Holte, et al found a positive association between amount of daily HA use and language outcomes.…”
Section: Developmental Outcomes and Service Provision In Children Witmentioning
confidence: 94%
“…Although the vast majority of infants are being screened for HL, an often stated concern is that children with mild HL are more likely to be underidentified or later identified compared with children with moderate-to-profound HL (Johnson et al, 2005;Ross et al, 2008). Late identification leads to later intervention (or no intervention at all), which puts children with mild HL at risk for academic, language, and social delays (Bess, Dodd-Murphy, & Parker, 1998;Blair et al, 1985;Most, 2004;Walker, Holte, et al, 2015;Yoshinaga-Itano et al, 2008).…”
Section: Nhs and Mild Hlmentioning
confidence: 99%
See 1 more Smart Citation
“…Since (i) the earliest diagnosis of hearing disorders, and (ii) the availability innovative technologies (particularly in terms of advanced hearing aids solutions), a progressive improvement of the rehabilitative results achieved in children affected by moderate-severe hearing loss has been observed in the last years [37] . Hearing aids in infancy have been recommended in case of bilateral SNHL, and in case of persistent conductive or mixed hearing loss [1,96,100,101] . Increasing evidences suggest a benefit of hearing aids use also in children with unilateral SNHL [102,103] and in some cases of auditory neuropathy [104] .…”
Section: Hearing and Speech Therapy Rehabilitationmentioning
confidence: 99%
“…If an adequate auditory stimulation is restored (i.e., by hearing aids, to rehabilitate a moderate-severe hearing loss), a reactivation of the neural synaptic connections may be possible, ensuring a regular auditory pathway development [93] . Hence, the early identification of hearing impairment in children and in particular within the first 3 months of life, is really important in order to set the proper and earliest therapeutical-rehabilitative plan [1,96,97] . If hearing loss is not recognized and corrected, it has been reported that scholastic learning and social activities may also be compromised, as well as emotional and psychological development [1,98] .…”
Section: Hearing and Speech Therapy Rehabilitationmentioning
confidence: 99%